111k views
4 votes
Simplify the radical expression (5+√3)(5-√3)

a. 16
b. 22
c. 25+10√3
d. 16+10√3

1 Answer

5 votes
The given expression is in the form (a+b)(a-b) where
a = 5
b = sqrt(3)

Recall that
(a+b)(a-b) = a^2-b^2
is the difference of squares formula

If a = 5, then a^2 = 25
If b = sqrt(3), then b^2 = (sqrt(3))^2 = 3
The squaring undoes the square root. The two opposites cancel out.

So using a^2 = 25 and b^2 = 3, we can say
(a+b)(a-b) = a^2-b^2 = 25-3 = 22

Therefore,
(5+sqrt(3))(5-sqrt(3)) = 22

Answer: B) 22
User Anshul Bisht
by
6.3k points